2018
DOI: 10.1111/jcmm.14021
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the SUMO code in the kidney

Abstract: SUMOylation of proteins is an important regulatory element in modulating protein function and has been implicated in the pathogenesis of numerous human diseases such as cancers, neurodegenerative diseases, brain injuries, diabetes, and familial dilated cardiomyopathy. Growing evidence has pointed to a significant role of SUMO in kidney diseases such as DN, RCC, nephritis, AKI, hypertonic stress and nephrolithiasis. Recently, emerging studies in podocytes demonstrated that SUMO might have a protective role agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 116 publications
(189 reference statements)
0
7
0
Order By: Relevance
“…26) One of the obvious functions of SUMO1 is its ability to bind to β-catenin and enhance transcriptional activity. 13) Moreover, the activation of β-catenin is closely related to the malignant transformation of colon and upper gastrointestinal adenocarcinoma. 27,28) Although Wnt signaling is not the mainstream inflammatory pathway, there is increasing evidence that it can be used as a driver of injury repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26) One of the obvious functions of SUMO1 is its ability to bind to β-catenin and enhance transcriptional activity. 13) Moreover, the activation of β-catenin is closely related to the malignant transformation of colon and upper gastrointestinal adenocarcinoma. 27,28) Although Wnt signaling is not the mainstream inflammatory pathway, there is increasing evidence that it can be used as a driver of injury repair.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In addition, SUMO1 is also involved in the regulation of signaling pathways such as nuclear factor-kappaB (NF-κB), Wnt/β-catenin, transforming growth factor-β (TGF-β) and c-Jun N-terminal kinase (JNK). 12,13) Based on the characteristics of SUMO1, it plays an important role in many diseases such as inflammation-related diseases, tumors, and kidney diseases. [14][15][16] In our study, we researched the role of resveratrol in inhibiting the expression of SUMO1 and the Wnt/β-catenin pathway in dextran sodium sulfate (DSS)-induced IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Sumoylation of proteins is an important regulatory element regulating protein function in the human body, which is involved in the pathogenesis of a variety of human diseases. More and more evidence have shown that sumoylation played important roles in the pathogenesis of diabetes [ 41 ]. However, we unexpectedly found that sumoylation of IGF-1R played a significant role in the process of stem cell osteogenic differentiation, especially in regulating downstream osteogenic-related transcription factors such as SNAI2 and RUNX2.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that SUMOylation and deSUMOylation play roles in numerous nephropathic diseases, such as renal dysgenesis, renal carcinoma, glomerular disease, podocyte apoptosis, renal medulla hypertonicity, acute kidney injury and nephrolithiasis 47‐51 . To clarify the relationship among KLF15, SUMO1, P53 SUMOylation and MC proliferation, we performed a series of transfection treatments on cells that had undergone PDGF‐BB‐induced proliferation.…”
Section: Discussionmentioning
confidence: 99%